Data Engineering on AWS: Data Cataloging, Processing, Analytics, and Visualization. - Kulshrestha, Dipali (linkedin.com, 2023)
Explore core concepts of data catalog, processing, analytics, and visualization in this second of a two-part series on data engineering with AWS.